Antibiotic Resistance Profiles and Molecular Characteristics of Extended-Spectrum Beta-Lactamase (ESBL)-Producing Escherichia coli and Klebsiella pneumoniae Isolated From Shrimp Aquaculture Farms in Kerala, India - Sivaraman, Gopalan Krishnan; Rajan, Vineeth; Vijayan, Ardhra; Elangovan, Ravikrishnan; Prendiville, Alison; Bachmann, Till T. (Frontiers in Microbiology, 2021)
This study was undertaken to evaluate the prevalence of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae in selected shrimp aquaculture farms (n=37) in Kerala, South India and to characterize the isolates using molecular tools. Overall, a low prevalence of ESBL-producers was found in the farms, most likely due to the reduced antibiotic usage in the shrimp farming sector. Out of the 261 samples (77 shrimp and 92 each of water and sediment), 14 (5.4%) tested positive for ESBL-E. coli or ESBL-K. pneumoniae. A total of 32 ESBL-E. coli and 15 ESBL- K. pneumoniae were recovered from these samples. All ESBL isolates were cefotaxime-resistant with minimal inhibitory concentration (MIC) ≥32 µg/ml. Of all isolates, 9 (28.1%) E. coli and 13 (86.7%) K. pneumoniae showed simultaneous resistance to tetracycline, ciprofloxacin and trimethoprim-sulfamethoxazole. PCR analysis identified CTX-M group 1 (blaCTX-M-15) as the predominant ESBL genotype in both E. coli (23, 71.9%) and K. pneumoniae (15, 100%). Other beta-lactamase genes detected were as follows: blaTEM & blaSHV (11 K. pneumoniae), blaCTX-M group 9 (9 E. coli) and blaCMY-2 (2 E. coli). Further screening for AMR genes identified tetA & tetB (13, 40.6%), sul1 (11, 34.4%), sul2 (9, 28.1%), catA & cmlA (11, 34.4%), qepA & aac(6')-Ib-cr (9, 28.1%) and strAB & aadA1 (2, 6.3%) in E. coli, and qnrB (13, 86.7%), qnrS (3, 20%), oqxB (13, 86.7%), tetA (13, 86.7%) and sul2 (13, 86.7%) in K. pneumoniae isolates. Phylogenetic groups identified among E. coli isolates included B1 (4, 12.5%), B2 (6, 18.8%), C (10, 31.3%), D (3, 9.4%) and E (9, 28.1%). PCR-based replicon typing (PBRT) showed the predominance of IncFIA & IncFIB plasmids in E. coli; however, in K. pneumoniae, the major replicon type detected was IncHI1. Invariably, all isolates of K. pneumoniae harboured virulence-associated genes viz., iutA, entB and mrkD. Epidemiological typing by pulsed-field gel electrophoresis (PFGE) revealed that E. coli isolates recovered from different farms were genetically unrelated, whereas isolates of K. pneumoniae showed considerable genetic relatedness. In conclusion, our findings provide evidence that shrimp aquaculture environments can act as reservoirs of multi-drug resistant E. coli and K. pneumoniae.